Advances in Artificial Intelligence 22nd Canadian Conference on Artificial Intelligence, Canadian AI 2009, Kelowna, Canada, May 25-27, 2009 Proceedings - Gao, Yong.; Japkowicz, Nathalie; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2009)
This book constitutes the refereed proceedings of the 22st Conference of the Canadian Society for Computational Studies of Intelligence, Canadian AI 2009, held in Windsor, Canada, in May 2008. The 30 revised full papers presented together with 5 revised short papers and 8 papers from the graduate student symposium were carefully reviewed and selected from 75 submissions. The papers present original high-quality research in all areas of Artificial Intelligence and apply historical AI techniques to modern problem domains as well as recent techniques to historical problem settings.
Invited Talks -- AI in Web Advertising: Picking the Right Ad Ten Thousand Times a Second -- Living with Constraints -- Computer (and Human) Perfection at Checkers -- Regular Papers -- Decision Tree Learning Using a Bayesian Approach at Each Node -- Generating Satisfiable SAT Instances Using Random Subgraph Isomorphism -- Enhancing the Bilingual Concordancer TransSearch with Word-Level Alignment -- Financial Forecasting Using Character N-Gram Analysis and Readability Scores of Annual Reports -- Statistical Parsing with Context-Free Filtering Grammar -- Machine Translation of Legal Information and Its Evaluation -- An Iterative Hybrid Filter-Wrapper Approach to Feature Selection for Document Clustering -- Cost-Based Sampling of Individual Instances -- Context Dependent Movie Recommendations Using a Hierarchical Bayesian Model -- Automatic Frame Extraction from Sentences -- Control of Constraint Weights for a 2D Autonomous Camera -- Training Global Linear Models for Chinese Word Segmentation -- A Concurrent Dynamic Logic of Knowledge, Belief and Certainty for Multi-agent Systems -- Enumerating Unlabeled and Root Labeled Trees for Causal Model Acquisition -- Compiling the Lexicographic Inference Using Boolean Cardinality Constraints -- Short Papers -- Improving Document Search Using Social Bookmarking -- Rank-Based Transformation in Measuring Semantic Relatedness -- Optimizing a Pseudo Financial Factor Model with Support Vector Machines and Genetic Programming -- Novice-Friendly Natural Language Generation Template Authoring Environment -- A SVM-Based Ensemble Approach to Multi-Document Summarization -- Co-Training on Handwritten Digit Recognition -- Evaluation Methods for Ordinal Classification -- STFLS: A Heuristic Method for Static and Transportation Facility Location Allocation in Large Spatial Datasets -- An Ontology-Based Spatial Clustering Selection System -- Exploratory Analysis of Co-Change Graphs for Code Refactoring -- Classifying Biomedical Abstracts Using Committees of Classifiers and Collective Ranking Techniques -- Large Neighborhood Search Using Constraint Satisfaction Techniques in Vehicle Routing Problem -- Valuable Change Detection in Keyword Map Animation -- The WordNet Weaver: Multi-criteria Voting for Semi-automatic Extension of a Wordnet -- Active Learning with Automatic Soft Labeling for Induction of Decision Trees -- A Procedural Planning System for Goal Oriented Agents in Games -- An Empirical Study of Category Skew on Feature Selection for Text Categorization -- Opinion Learning without Emotional Words -- Belief Rough Set Classifier -- Graduate Student Symposium -- Automatic Extraction of Lexical Relations from Analytical Definitions Using a Constraint Grammar -- Grid-Enabled Adaptive Metamodeling and Active Learning for Computer Based Design -- Reasoning about Movement in Two-Dimensions -- Executable Specifications of Fully General Attribute Grammars with Ambiguity and Left-Recursion -- - : A Semantic Web Based Knowledge Representation and Context-Driven Morphing Framework -- Background Knowledge Enriched Data Mining for Interactome Analysis -- Modeling and Inference with Relational Dynamic Bayesian Networks -- A Semi-supervised Approach to Bengali-English Phrase-Based Statistical Machine Translation.
Keywords: Data mining; Natural language processing (Computer science).; Pattern recognition systems; Artificial intelligence; Biometric identification; Computers and civilization; Data Mining and Knowledge Discovery; Natural Language Processing (NLP).; Automated Pattern Recognition; Artificial Intelligence; Biometrics; Computers and Society